1984
DOI: 10.1002/ijc.2910340310
|View full text |Cite
|
Sign up to set email alerts
|

Paired epstein‐barr virus‐carrying lymphoma and lymphoblastoid cell lines Burkitt's lymphoma patients: Comparative sensitivity to non‐specific and to allo‐specific cytotoxic responses in vitro

Abstract: Paired Epstein-Barr (EB) virus-carrying cell lines have been established from Burkitt's lymphoma (BL) patients; one the BL-cell line derived from the malignant cells of the tumour and bearing the relevant chromosomal translocation, the other the diploid lymphoblastoid cell line (LCL) derived from the patient's normal B cells by experimental infection with the virus. Comparative studies have shown that both BL and LCL cells are relatively resistant to fresh NK cells but are more susceptible to in vitro-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…This is not due to a general resistance to cell-mediated cytotoxicity. BL/LCL pairs derived from the same donor and kept in culture during similar periods were equally sensitive to natural and interferon-activated killer cells (20,32). This was also true for the cell lines used in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is not due to a general resistance to cell-mediated cytotoxicity. BL/LCL pairs derived from the same donor and kept in culture during similar periods were equally sensitive to natural and interferon-activated killer cells (20,32). This was also true for the cell lines used in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…We have used "trios" composed of an in vitro-transformed LCL, an EBV-negative BL line, and an EBV-converted subline of the latter, derived from the same patient, and "duos" consisting of a LCL and an EBV-carrying BL (18)(19)(20). The CTL clones were generated by stimulation with autologous and allogeneic EBV-infected B cells.…”
mentioning
confidence: 99%
“…They are as sensitive to natural killer cells and to interferon-and mixed lymphocyte culture-activated nonspecific killer cells as were the corresponding LCLs (9,22). Moreover, as shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…IARC-BL18, BL72, BL74 and Elija are Burkitt's lymphoma cell lines (Rooney et al, 1984(Rooney et al, , 1985 kindly given by G.M.Lenoir and A.B.Rickinson. PRBL18 is a human lymphoblastoid cell line made by infecting peripheral lymphocytes from a seronegative English donor with EBV from BL18 (Rooney et al, 1984(Rooney et al, , 1985. Raji cells are derived from an African Burkitt's lymphoma (Pulvertaft, 1965).…”
Section: Methodsmentioning
confidence: 99%